2019
DOI: 10.1007/s11302-019-09680-3
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic signaling in hepatic disease

Abstract: Extracellular purines (ATP and adenosine) are ubiquitous intercellular messengers. During tissular damage, they function as damage-associated molecular patterns (DAMPs). In this context, purines announce tissue alterations to initiate a reparative response that involve the formation of the inflammasome complex and the recruitment of specialized cells of the immune system. The present review focuses on the role of the purinergic system in liver damage, mainly during the onset and development of fibrosis. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 109 publications
1
16
0
Order By: Relevance
“…In agreement with this observation, in vitro studies have shown that IL-1β treatment induced lipid accumulation in hepatocytes and the activation of fibrogenesis in hepatic stellate cells [28,37]. In the liver, hepatocytes, stellate, and Kupffer cells all express the NLRP3 inflammasome being activated after liver injury to determine the maturation and release of IL-1β, IL-18, and the following cascade of other inflammatory cytokines, favoring liver inflammation and fibrosis [38].…”
Section: P2x7 Receptor Nlrp3 Inflammasome Nafld and Liver Fibrosissupporting
confidence: 53%
See 3 more Smart Citations
“…In agreement with this observation, in vitro studies have shown that IL-1β treatment induced lipid accumulation in hepatocytes and the activation of fibrogenesis in hepatic stellate cells [28,37]. In the liver, hepatocytes, stellate, and Kupffer cells all express the NLRP3 inflammasome being activated after liver injury to determine the maturation and release of IL-1β, IL-18, and the following cascade of other inflammatory cytokines, favoring liver inflammation and fibrosis [38].…”
Section: P2x7 Receptor Nlrp3 Inflammasome Nafld and Liver Fibrosissupporting
confidence: 53%
“…The discovery of the NLRP3 inflammasome, together with the role of ATP and P2X7 receptors in the processing and release of mature IL-1β, has provided the connection between extracellular ATP, P2X7 receptor, NLRP3 inflammasome, and IL-1β release and the activation and amplification of the inflammatory process. To this regard NLRP3 activation has been described as a "two-step" process: the first is via an NFkB activator as well as LPS, while the second step is mainly via the so-called DAMPs, distinct molecules released by damaged cells acting as alert signals to trigger the innate immune response [38]. As detailed above, among the different DAMPs extracellular ATP (via the activation of the P2X7 receptor on target cells) is one of the most studied, although other activators have been reported, such as reactive oxygen species (ROS), crystals, or large particles [27,34].…”
Section: P2x7 Receptor Nlrp3 Inflammasome Nafld and Liver Fibrosismentioning
confidence: 99%
See 2 more Smart Citations
“…Drugs that selectively target P2X4 channels equally offer therapeutic potential [ 105 , 106 ]. P2X4 channels mainly mediate the trafficking of calcium ions in response to ATP and are involved in different pathologies [ 105 , 107 , 108 , 109 ]. Given the lack of specific and potent P2X4-antagonists, studies have focused on the generation of nanobodies directed towards P2X4 [ 84 ].…”
Section: Antibodies and Nanobodies To Target Cell Plasma Membrane mentioning
confidence: 99%